Travails of tracheostomy - Srinivas, C. V.; Goel, Tanubha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Tracheostomy is a surgical procedure which consists of making an incision on the anterior aspect of the neck and opening a direct airway through an incision in the trachea. Methods: This was a prospective study which included 50 patients who underwent tracheostomy between September 2020 to April 2022. Our study was aimed to report the most common indications, complications, outcomes in tracheostomised patients. For evaluation of patients undergoing tracheostomy, a database was created which included demographic profile of the patient such as age, gender, diagnosis as well as indication, complications which were divided into early, intermediate and late complications and day of decannulation. Results: Among 50 patients, 41 (82%) were males and 9(18%) patients were females. The age of the patients included in this study ranged from 20 to 80 years. Majority were in age group between 40 to 60 years (48%). Out of 50 patients, 39 (78%) patients underwent tracheostomy due to prolonged intubation (CVA, head injury, organophosphorus poisoning, respiratory failure), 11 (22%) for upper airway obstruction due to malignancy. Conclusions: In this study 40 to 60 years was the most common age group for which tracheostomy was done. It was done more in males. Most common indication for tracheostomy was prolonged ventilation followed by malignancy. Incidence of complications was 76%. Most common early complication observed was haemorrhage, most common intermediate complication was tube blockage and most common late complication was tracheoesophageal fistula. Mortality occurred in 6 patients. To conclude even today tracheostomy remains the lifesaving procedure and complications of tracheostomy are largely preventable.